Measuring Reaction Dividend Announcement to Trading Volume Activity in Companies Listed in IDXHIDIV20 Index - Rizki, Ahmad; Sudarsono, Bambang (Eco-Entrepreneur, 2023)
The purpose of this study was to determine whether there are differences in stock trading volume as a result of the effect of dividend distribution announcement on companies listed on the Indonesian Stock Exchange (IDX) and those incorporated in the IDXHIDIV20 index from 2019-2021 This research was conducted using quantitive methods. The analysis used in event study. The data used in this study were secondary data obtained from the IDX with a sampling technique using a purposive sampling method, and a total sample of 7 companies was obtained, namely: Bank Negara Indonesia (Persero) Tbk, Bank Rakyat Indonesia (Persero) Tbk, Bank Mandiri (Persero) Tbk, Hanjaya Mandala Sampoerna Tbk, Indofood Sukses Makmur Tbk, Bukit Asam Tbk, Telekomunikasi Indonesia Tbk. The hypotesis testing used in the Kolmogorov Smirnov analysis using the SPSS program. The results ofthe Wilcoxon Signed Ranked Test show that the announcement of dividend distribution has no efect on stock trading volume, which means thet the hypotesis is accepted.